The Heart Still Singing: Raymond Souster at 82 - Tremblay, Tony (Studies in Canadian Literature, 2002)
Poet Raymond Souster looks back over almost seventy years of poetry, discussing his very early development as a poet, his involvement with literary magazines, and his work as an anthologist. He discusses his relationships with Irving Layton and Louis Dudek, their work together, and their attempt to institute a new Canadian poetics. Souster speaks of the critical reception to his work, and argues that philosophy has no place in poetry.